Futsal injuries: A 7-season incidence and characteristics - Keiichi Yoshida; Tomohiko Tateishi; Yusuke Morimoto (Elsevier, 2023)
Summary: Objectives: Most literatures describe the injury incidence in futsal during the matches, however, the true injury incidence in matches and trainings through the season is unclear. Study design: Descriptive Epidemiology Study. Method: We investigated all injuries suffered by one futsal team in Japan after each match or training session. The number of injuries, player position, circumstances, severity, incidence and burden per 1000 player hours, locations and types of injuries were examined. Results: A total of 518 injuries were reported during the trainings (302, 58.3%) and matches (216, 41.7%). Overall, injury incidence per 1000 player hours was 16.4 and incidence during the match (90.4) was nearly 9 times higher than during training (10.4). Total injury burden per 1000 player hours was 124.7. Injury burden was approximately 10 times higher during matches (725.8) than during training (75.4). Winger had a higher rate of injuries (267, 51.5%) and Goalkeeper had a lower injury rate (50, 9.7%). Contact injuries (278, 53.7%) and non-contact injuries (240, 46.3%) each accounted for nearly half of all injuries. More than a third of the injuries were caused by time-loss injuries (194, 37.5%). The most common injuries sustained during matches and trainings were to the lower limbs (375, 72.4%). During matches, there were more contusions and less overuse than during trainings. Ankle sprain/ligament injuries were the most common diagnoses (59, 11.4%). Conclusions: This study clarified the injury incidence and characteristics that occurred in futsal through trainings and matches. Based on this finding, preventive interventions for specific injury risks may be possible in the future.